Study of the blood supply of the brain in sheep - Kadhum, Khalid Kamil (The Iraqi Journal of Veterinary Medicine, 1999)
The brain of the sheep receives its blood supply through the carotid rete and the basilar artery. The carotid rete formed of contribution of internal carotid artery and branches from maxillary artery. The internal carotid artery courses on the ventral surface of the cerebal crus to give the rostral cerebal artery and the caudal communicating artery . Thus , arteries excepted the middle cerebal artery forming with the same arteries of the opposite side , the cerebal arterial circle or circle of Willis. The internal caroted artery also gives off hypophysialartery to the 1999 ind, (1) swell, ügymielly wel dati’, il pellilendiambell ileti hypophysis. The caudal communicating artery give off the caudal cerebal artery and the rostral cerebellar artery and unite with the corresponding artery of the opposite side to form the basilar artery rostral to the pone . The basilar artery gives off the pontine artery , caudal cerebellar artery and the medullary branch.